Reciprocal muscle group and functional dynamic stability ratios of the hamstrings and quadriceps muscle groups during maximal isokinetic concentric and eccentric contractions - Surmon, Sean Henry (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Mbk.) -- University of Stellenbosch, 1999.